2023
DOI: 10.1186/s12893-023-02012-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the therapeutic effect of dressing containing Silver (Ag coat) in the process of healing skin blisters caused by limb fractures: a clinical trial study

Abstract: Background The main activity of the skin is to create a protective barrier against damage. Loss of the skin due to injury or disease and failure to regenerate the affected area may result in disability, infection, or even death. We conducted a clinical trial to evaluate the therapeutic effect of dressing containing silver in process of healing skin blisters caused by limb fractures. Method This is a pioneering randomized trial that compares the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Patients treated with this dressing experienced less pain and a significantly shorter wound healing time compared to those treated with Gaz Vaseline. 169 In a clinical trial assessing the efficacy of CuO-impregnated foam polymer dressings in preventing postoperative wound infection, patients using the Cu dressings had significantly lower rates of wound infection compared to those using non-Cu dressings. 170 In the controlled clinical trial using the SilvrSTAT Gel, a significant reduction in wound size was observed after 2 weeks of use and almost complete healing was achieved after 8 weeks.…”
Section: Clinical Application Of Mnpsmentioning
confidence: 99%
“…Patients treated with this dressing experienced less pain and a significantly shorter wound healing time compared to those treated with Gaz Vaseline. 169 In a clinical trial assessing the efficacy of CuO-impregnated foam polymer dressings in preventing postoperative wound infection, patients using the Cu dressings had significantly lower rates of wound infection compared to those using non-Cu dressings. 170 In the controlled clinical trial using the SilvrSTAT Gel, a significant reduction in wound size was observed after 2 weeks of use and almost complete healing was achieved after 8 weeks.…”
Section: Clinical Application Of Mnpsmentioning
confidence: 99%